2017
DOI: 10.5897/ajb2017.16261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Roselle (Hibiscus sabdariffa) and ginger (Zingiber officinale) as feed additives, on growth and haematology of Clarias gariepinus Juvenile

Abstract: The rebirth and use of medicinal plants in aquaculture has become necessary as the use of synthetic drugs and chemicals is been discouraged due to their aftermath effects on cultured organisms and aquatic environment. A 56-day study was conducted to assess the effects of Roselle and ginger as dietary additives, on growth and hematology of Clarias gariepinus juvenile. Total of 150 C. gariepinus juveniles (35.41±1.45 g) were assigned to five iso-nitrogenous diets as treatments having ginger and roselle added as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…It has been reported for antioxidants and protective role against toxicants, insecticidal, antimicrobial and antiprotozoal activities [11][12][13][14]. It has also been recently been reported to improve growth performances in experimental animals [15]. It is considered as a safe herbal medicine with only few and insignificant side effects [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported for antioxidants and protective role against toxicants, insecticidal, antimicrobial and antiprotozoal activities [11][12][13][14]. It has also been recently been reported to improve growth performances in experimental animals [15]. It is considered as a safe herbal medicine with only few and insignificant side effects [16].…”
Section: Introductionmentioning
confidence: 99%
“…The weight gained might be due to the addition of roselle in the diets of the fish. Earlier studies by Ogueji et al (2017) and Kumar et al (2014) reported that plants have growth promoters for use in fish nutrition. Findings from this study agrees with Ogueji et al (2017) who obtained higher growth performance from C. gariepinus juvenile fed roselle and ginger supplemented diets compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies by Ogueji et al (2017) and Kumar et al (2014) reported that plants have growth promoters for use in fish nutrition. Findings from this study agrees with Ogueji et al (2017) who obtained higher growth performance from C. gariepinus juvenile fed roselle and ginger supplemented diets compared to the control. Furthermore, findings of this study agrees with earlier report by Adewole, (2014) who observed increased in growth parameters in C. gariepinus fed diet incorporated with roselle compared with the control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are various reports of herbal fish diets promoting growth performance (Ji et al, 2007;Dada, 2012), increasing stress tolerance (Ji et al, 2009), and enhancing immune system effectiveness (Bai et al, 2009;Abdel-Tawwab et al, 2018). More recently such applications have begun to demonstrate positive effects in feeds for various fish species including African catfish, (Clarias gariepinus) (Turan & Akyurt, 2005;Turan & Çek, 2007;Turan & Yigitarslan, 2016;Ogueji et al, 2017), tilapia (Oreochromis aureus) (Turan, 2006), (Oreochromis niloticus) (Rawling et al, 2009), common carp (Cyprinus carpio) and crayfish (Astacus leptodactylus) (Turan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%